PENGUATAN KREATIVITAS MAHASISWA DALAM KEGIATAN KEWIRAUSAHAAN MELALUI PROGRAM INKUBASI DAN PELATIHAN BERBASIS PROYEK - Hansly, Hansly; Meitiana, Meitiana (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Creativity is one of the key elements in the development of entrepreneurship among students. Students as the younger generation are not only required to have business ideas, but also the ability to create innovations that are worth selling. This community service activity aims to build and increase students' creativity in designing and implementing entrepreneurial ideas through project-based learning and business incubation programs. The activity was carried out within the Faculty of Economics and Business, University of Palangka Raya, involving 40 students from various study programs. Implementation methods include creative training, brainstorming ideas, business simulations, and product prototyping. The results of the activity show that training designed in a participatory manner is able to improve students' ability to initiate innovative, market-oriented, and local potential-based products. In addition, the involvement of lecturers as mentors also provides significant support for the success of the training. It can be concluded that student creativity in entrepreneurship needs to be facilitated in a sustainable manner through a supportive campus ecosystem, ranging from training, mentoring, to market access.